Factors affecting rule compliance with mesh size regulations in the Baltic cod trawl fishery - Suuronen, Petri; Tschernij, Vesa; Jounela, Pekka; Valentinsson, Daniel; Larsson, P-O. (ICES Journal of Marine Science, 2007)
<qd> Suuronen, P., Tschernij, V., Jounela, P., Valentinsson, D., and Larsson, P-O. 2007. Factors affecting rule compiance with mesh size regulations in the Baltic cod trawl fishery. – ICES Journal of Marine Science, 64. </qd>In this study, we evaluate the efficiency and applicability of a series of gear-based management measures, enforced since 1990, whose purpose was to improve size selectivity in the trawl fishery for Baltic cod ( Gadus morhua ). In general, our study revealed that these measures had no marked effect on the capture and discard of young cod. Legal and illegal manipulation of selective codends was widespread. The adoption of a codend design that offered a modest increase in selectivity, but had a good match with the legislated minimum landing size (MLS), led to greater compliance, demonstrating that a mismatch between MLS and selectivity should be avoided. It was also obvious that, generally, the fishing industry did not tolerate large short-term losses. Our evaluation is that overly ambitious rules will be circumvented, and frequent and incoherent changes in the regulations represent bad management practice. A gradual introduction of restrictions and participation by fishers in the decision-making process will increase compliance.